PlantSat: a specialized database for plant satellite repeats - Macas, Jirí; Mészáros, Tibor; Nouzová, Marcela (Bioinformatics (Oxford, England), 2002)
MOTIVATION: Tandemly organized repetitive sequences (satellite DNA) are widespread in complex eukaryotic genomes. In plants, satellite repeats often represent a substantial part of nuclear DNA but only a little is known about the molecular mechanisms of their amplification and their possible role(s) in genome evolution and function. Unfortunately, addressing these questions via characterization of general sequence properties of known satellite repeats has been hindered by a difficulty in obtaining a complete and unbiased set of sequence data for this analysis. This is mainly due to the presence of multiple entries of homologous sequences and of single entries that contain more than one repeated unit (monomer) in the public databases. RESULTS: We have established a computer database specialized for plant satellite repeats (PlantSat) that integrates sequence data available from various resources with supplementary information including repeat consensus sequences, abundances, and chromosomal localizations. The sequences are stored as individual repeat monomers grouped into families, which simplifies their computer analysis and makes it more accurate. Using this feature, we have performed a basic sequence analysis of the whole set of plant satellite repeats with respect to their monomer length and nucleotide composition. The analysis revealed several preferred length ranges of the monomers (approximately 165 bp and its multiples) and an over-representation of the AA/TT dinucleotide in the repeats. We have also detected an enrichment of satellite DNA sequences for the motif CAAAA that is supposed to be involved in breakage-reunion of repeated sequences.
Keywords: Plants; uživatelské rozhraní počítače; internet; User-Computer Interface; databáze nukleových kyselin; Databases, Nucleic Acid; výpočetní biologie; Sequence Analysis, DNA; sekvenční analýza DNA; automatizované zpracování dat; Software; Internet; rostliny; DNA rostlinná; DNA, Plant; satelitní DNA; DNA, Satellite; software; Electronic Data Processing; Computational Biology